Spontaneous Hetero-attachment of Single-Component Colloidal Precursors for the Synthesis of Asymmetric Au-Ag2X (X = S, Se) Heterodimers - Lin, Mengxi (Chemistry of materials : a publication of the American Chemical Society, 2022)
© 2022 The Authors. Published by American Chemical Society.